Initial Characterization of Alkaline Protease from Pseudomonas sp Isolated from Chicken Feces (POSTER) - Yuyun Firdausi Nuzulah; Suharti Suharti (Jurnal Kimia Riset, 2018)
Abstract Proteases are ubiquitous enzymes and it can be found in all living organisms. Extracellular proteases have high economic value, where the enzymes can be applied to various industrial sectors. In order to find an alternative source of protease, a search for microbe producing extracellular protease has been done using a selective medium. An extracellular producing bacterium that is identified as Pseudomonas sp has been isolated from chicken feces, that is Gallus gallus bankiva, collected from residential areas at Lowokwaru, Malang, Indonesia. The analysis shows that the bacterium produces extracellular protease with optimum activity after incubation of 66 hours at 35oC. Initial characterization of the extracellular protease shows that the extracellular protease produced by Pseudomonas sp has an optimum activity at pH 12 and an optimum temperature at 39oC. At these conditions, the crude extract enzyme has a specific activity of 0,522 U/mg. The high pH resistance allows its application to variety of industrial processes that require high pH operation. Therefore further studies need to be done to get better understanding of enzyme properties.  Keywords: Alkaline protease, Chicken feces, Gallus gallus bankiva, Pseudomonas sp